Diversity of Soil Macrofauna on Various Stand Types in Gunung Walat University Forest, Sukabumi, West Java - Cahyo Wibowo; Wardatur Rizqiyah (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2014)
Soil macrofauna is part of the soil biodiversity that plays an important role in the improvement of the physical, chemical, and biological properties of soil through the process of immobilisation and humification. Soil macrofauna have roles in the process of fragmentation, as well as providing environmental facilities (microhabitat) for facilitating the decomposition process which is conducted by soil mesofauna and microfauna and various types of bacteria and fungi. The aim of this research is to identify and measure the diversity of soil macrofauna in different types of forest stands of Gunung Walat University Forest (dense and sparse agathis stand, dense and sparse pine stand which were either burnt or not burnt, and dense and sparse mixed stand). The study showed that the highest abundance was in the stand of dense Agathis. Mixed stand (mixture of Agathis, Pine and Altingia excelsa) showed the highest soil macrofauna diversity. The classes of Oligochaeta and Geophilomorpha were most commonly found on every type of stand in Gunung Walat University Forest.